1 - MENTAL HEALTH PLANNING IN AFRICA : Isäues and Strategy - ERINOSHO, Olayiwola A. (Africa Development, 1979)
In the preceding article, the author examines the important problem of mental health planning in Africa. Its purpose is to show us that mental health planning as it is conceived in developed European and American countries is not the only way that can guarantee us success in this area. He introduces his subject by pointing out that the real obstacle to development in Africa is that development there is conceived as a blind imitation of technologically advanced societies, while African countries do not have the necessary resources capable of producing such development. In the specific case of mental health planning, Africa has yielded to the easier temptation to adopt the ideology and therapeutic principles for mental illness of the developed European countries. His analysis is articulated in three main points: In the first part, he compares the forms of treatment of the mentally ill based on the internment of the latter in a hospital and those which keep them in their community. The second part is devoted to the comparison of the forms of treatment which cut them off from their cultural environment with those which take place in this cultural environment. In the third part, he suggests a strategy to prevent mental illnesses.